STUDY OF DETERMINANTS OF MATERNAL HEALTH CARE COVERAGE IN RURAL AREA OF DISTRICT BARABANKI, UTTAR PRADESH - Dr. Bhupesh Kori; Dr Neeti verm; Dr. Nirpal Kaur Shukl; Dr. Zainab khan; Dr M.P. Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
AbstractBackground: Women and children constitute a large proportion of any population. They are the most vulnerable to morbidity and mortality especially in developing countries. In many situations the problem of poor maternal and child health stems from the poor use of available services even when they are not of optimum quality. Methods: The study used a cross-sectional analytic design. Pretested semi structured questionnaires were administered by interviewers to 540 women from a rural area of district Barabanki. Chi square analysis was done to identify factors associated with Maternal and Child Health Service utilization. Logistic regression was used to identify determinants of utilization patterns. Results: The study revealed that increasing age, educational level, occupation of both women and their husbands were associated with increased MCH service utilization Conclusions: Improved use of MCH services is related to socio economic challenges women face such as illiteracy and low income. The way health facilities and their staff are perceived by rural women affect how they use some of these services and should be considered in programs which seek to reduce maternal and child mortality.